Efforts to Improve Student Learning Outcomes Through Learning-Based Models Problems in Science Subjects: Upaya Meningkatkan Hasil Belajar Siswa Melalui Model Pembelajaran Berbasis Masalah pada Mata Pelajaran IPA - Endang Triwanis Can (International Journal of Technology Vocational Education and Training, 2020)
A classroom action research has been carried out at SMP Negeri 1 Koto Baru with the aim of improving science learning outcomes through the Problem Based Learning (PBL) model. Learning has been taking place conventionally, this has resulted in learning outcomes not being maximized as expected. This classroom action research was carried out for two cycles with each cycle having two meetings. Every time the learning process meets with a problem-based learning model (Problem Based Learning / PBL). As data collection instruments are student worksheets, daily test sheets and observation sheets filled with observers, with steps for planning action, implementing actions, observing, evaluating and reflecting for each cycle. Based on the research results, it was found that the average increase in student learning outcomes through the problem-based learning model (Problem Based Learning / PBL) in the initial conditions averaged 63.7 or the percentage of KKM achievement was 40% in cycle I increased by 70.8 or the percentage of KKM achievement 53.3% and in cycle II increased to 79.3 or 83.3%. Student learning outcomes have increased from the first cycle to the second cycle. Each individual practice value for each meeting has increased. The end of the cycle held daily tests also increased. Learning using a problem-based learning model (Problem Based Learning / PBL) has a positive impact on student learning outcomes.